Robotics Has a Race Problem. (May 2020) - Sparrow, Robert
If people are inclined to attribute race to humanoid robots, as recent research suggests, then designers of social robots confront a difficult choice. Most existing social robots have white surfaces and are therefore, I suggest, likely to be perceived as White, exposing their designers to accusations of racism. However, manufacturing robots that would be perceived as Black, Brown, or Asian risks representing people of these races as slaves, especially given the historical associations between robots and slaves at the very origins of the project of robotics. The only way engineers might avoid this ethical and political dilemma is to design and manufacture robots to which people will struggle to attribute race. Doing so, however, would require rethinking the relationship between robots and "the social, " which sits at the heart of the project of social robotics. Discussion of the race politics of robots is also worthwhile because of the potential it has to generate insights about the politics of artifacts, the relationship between culture and technology, and the responsibilities of engineers.